ジキケン プラズマ ト オーロラ サブストーム ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 大家, 寛; オオヤ, ヒロシ; OYA, Hiroshi (国立極地研究所, 1972)
P(論文) A recommendation to scientific objectives of the polar rocket measurements is presented with respect to studies on the relationship between the magnetospheric plasma and the aurora breakup stages or substorms. The qualitative consideration on the wave-particle interaction in a turbulence involving the plasma instability and nonlinear interactions suggests a possibility of energetic aurora particle production in the magnetospheric plasma. This should be investigated quantitatively using a correlated observation system established between the polar rockets and the orbiting satellites in the magnetosphere. Conventional parameters, which describe the aurora and the substorm, such as the magnetic field, particle energy spectrum, electron density and photo-chemical productions, should also be measured by the rockets, while the electric field spectrum in the turbulent plasma will be measured by the satellites being correlated with the energetic particle spectrum in the magnetosphere. departmental bulletin paper